Translation Typology and the Interdisciplinarity of Translatology - Floros, Georgios (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn this paper the issue of interdisciplinarity in translatology is discussed in relation to the problem of translation typology, and it is suggested that typology is not only a core theoretical issue in any discipline, but also an important point of reference for the interaction of translatology with other disciplines. This paper should be seen as an attempt to rethink the types of translation, as this is, among others, an area where interdisciplinarity finds a sound expression. Up until now other disciplines have set the pace in the typology of translation and the texts to be translated (e.g. linguistics, genre-theory), whereas it is rather criteria internal to the field of translation studies that should be established in order to generate a more meaningful typology, based on the relationship between text and background knowledge.